Light-Responsive and Antibacterial Graphenic Materials as a Holistic Approach to Tissue Engineering - Ferreras, Andrea; Matesanz, Ana; Mendizabal, Jabier; Artola, Koldo; Nishina, Yuta; Acedo, Pablo; Jorcano, José L.; Ruiz, Amalia; Reina, Giacomo; Martín, Cristina (ACS Nanoscience Au, 2024)
While the continuous development of advanced bioprinting technologies is under fervent study, enhancing the regenerative potential of hydrogel-based constructs using external stimuli for wound dressing has yet to be tackled. Fibroblasts play a significant role in wound healing and tissue implants at different stages, including extracellular matrix production, collagen synthesis, and wound and tissue remodeling. This study explores the synergistic interplay between photothermal activity and nanomaterial-mediated cell proliferation. The use of different graphene-based materials (GBM) in the development of photoactive bioinks is investigated. In particular, we report the creation of a skin-inspired dressing for wound healing and regenerative medicine. Three distinct GBM, namely, graphene oxide (GO), reduced graphene oxide (rGO), and graphene platelets (GP), were rigorously characterized, and their photothermal capabilities were elucidated. Our investigations revealed that rGO exhibited the highest photothermal efficiency and antibacterial properties when irradiated, even at a concentration as low as 0.05 mg/mL, without compromising human fibroblast viability. Alginate-based bioinks alongside human fibroblasts were employed for the bioprinting with rGO. The scaffold did not affect the survival of fibroblasts for 3 days after bioprinting, as cell viability was not affected. Remarkably, the inclusion of rGO did not compromise the printability of the hydrogel, ensuring the successful fabrication of complex constructs. Furthermore, the presence of rGO in the final scaffold continued to provide the benefits of photothermal antimicrobial therapy without detrimentally affecting fibroblast growth. This outcome underscores the potential of rGO-enhanced hydrogels in tissue engineering and regenerative medicine applications. Our findings hold promise for developing game-changer strategies in 4D bioprinting to create smart and functional tissue constructs with high fibroblast proliferation and promising therapeutic capabilities in drug delivery and bactericidal skin-inspired dressings.